Rasch Analysis of the Force and Motion Conceptual Evaluation Test: Validity and Reliability in Measuring Force and Motion Understanding of Students - Basri, Nur Akhyar; Salmah, Ummi; Irawan, Ivan Danar Aditya; Indraloka, Ristanti Mulia; Parno, Parno (Jurnal Pembelajaran Fisika, 2024)
Understanding Force and Motion is fundamental in physics education as it forms the basis for more complex concepts and has practical applications in various fields, from engineering to everyday problem-solving. This paper aims at assessing the quality of test questions using the Rasch model to gauge students' understanding of Force and Motion within physics education. The significance of accurately assessing these concepts cannot be overstated, as it ensures that students have a solid foundation for future learning. Adopting a descriptive qualitative approach, the research employed the FMCE (Force and Motion Conceptual Evaluation) test instrument alongside Rasch modelling. The study involved 35 high school students who had covered the Force and Motion curriculum. Analysis with Winstep software (Version 3.65.0) revealed that items 1 and 7 were invalid. The instrument demonstrated commendable reliability, with an item reliability of 0.73. Difficulty level analysis identified five questions as outliers, categorised as either very difficult or very easy. The discrimination analysis confirmed that the instrument effectively differentiated between students who answered correctly and those who did not. Overall, the FMCE exhibited solid validity and high reliability, although some items necessitate revision. The study's limitations, particularly the small sample size, may affect the generalisability of the findings. Despite these limitations, the study provides valuable insights into the assessment of Force and Motion concepts in high school students, though caution is advised when interpreting the results. Future research should consider a larger sample size and diverse educational contexts to enhance the robustness and applicability of the findings.Keywords: Concept understanding, force and motion, high school students, instrument test, Rasch modelDOI: http://dx.doi.org/10.23960/jpf.v12.n1.202404